(untitled) (REMUNOM, 2025)
Introduction: Smoking is recognized as one of the main modifiable risk factors for the development of non-communicable chronic diseases. Primary health care, due to its resolutive nature and continuous care, represents the main point of contact for these individuals. Objective: To discuss the role of the multiprofessional team in health education focused on smoking management in patients with chronic obstructive pulmonary disease, with an emphasis on promoting self-care, preventing exacerbations, and improving the quality of life of these users within the scope of primary health care. Methodology: This is a descriptive literature review. Data collection was conducted through searches in electronic scientific databases such as SciELO and Google Scholar. Articles published between 2019 and 2025 were included. Results and Discussions: Several authors highlight that, when integrated and well-structured, the multiprofessional approach favors patient adherence to treatment. They also point out several challenges faced in the daily routine of basic health units. Among the main obstacles are low user adherence, especially in advanced stages of chronic obstructive pulmonary disease, the scarcity of trained professionals to properly address nicotine dependence, limited consultation time, and lack of continuity in educational actions. Conclusion: The multiprofessional approach in primary health care has proven essential for the effective management of smoking in patients with chronic obstructive pulmonary disease. The inclusion of digital technologies and psychological support have also shown to be important allies in the smoking cessation process. Keywords: Smoking; Chronic Obstructive Pulmonary Disease; Health Education; Primary Health Care; Multiprofessional Team.